Uji validitas model shrinking core terhadap pengaruh konsentrasi asam sitrat dalam proses leaching nikel laterit - Kevin Cleary Wanta; Himawan T. B. M. Petrus; Indra Perdana; Widi Astuti (Jurnal Rekayasa Proses, 2017)
Atmospheric pressure acid leaching process is one of nickel laterite processing which has a big potential to be applied in industry. The leaching process is influenced by several factors and one of them is concentration of acid as leachant. The purpose of this present study is to learn the effect of concentration of citric acid on the use of shrinking core kinetic model. The process was done by varying citric acid concentration at 0.1, 1, and 2 M. The other operation conditions, such as particle size, solid-liquid ratio, temperature, stirring speed, and leaching process were kept constant at 125-150 μm, 0,2 sample mass/volume of acid solution, 85 oC, 200 rpm, and 120 minutes, respectively. The experimental results showed that the higher concentration of citric acid was used, the higher the percentage recovery of nickel was obtained. In addition, the validity test of shrinking core model indicated a positive impact to describe physical phenomenon of leaching process.